Cultural Differences And Learner Strategies In Enhancing Student’s Communication Skills - alfian alfian (English Language, Linguistics, Literature, And Education Journal, 2019)
Written and verbal Communication skill in English is highly important in entering the global world. For this reason the Indonesian government has made English as a compulsory subject from secondary school to tertiary level. Instead of a lot efforts have been done in enhancing English communication ability, most of Indonesian students are far from being able to communicate in English. This may be closely related to the strategies that they choose in improving their communicative skills. Indonesia English learner tends to choose memory strategy in improving their English in general while other strategies such as metacognitive and social strategies are rarely employed by Indonesian learner. This phenomena might be closely related to the several critical factors, such as, characteristic of Indonesian student, passive learner, and the most important factor is that might be related to teaching and learning practice in the classroom in which it is constructed based on the Large power distance culture where teacher is regarded to be the one who is knowledgeable and students is like a bottle that need to be filled up with the knowledge. As a result, classroom teaching practice tends to adopt teacher centred approach in which teacher transfers knowledge to the students. This model of teaching is far from being developing student’s strategies in improving their communication skill while students learn through the way teacher delivers the lesson in the classroom. Therefore, this paper briefly overviews the student’s lack of using certain strategies in improving their communicative skill as the impact of teacher centred approach in which resulted from Large power distance culture. The alternative ways of approaching student’s learner strategies and teaching practice will also be addressed at the end of this paper.